Exploring the differential effects of trust violations in human-human and human-robot interactions. (May 2021) - Alarcon, Gene M.; Gibson, Anthony M.; Jessup, Sarah A.; Capiola, August
Abstract: There is sparse research directly investigating the effects of trust manipulations in human-human and human-robot interactions. Moreover, studies on human-human versus human-robot trust have leveraged unusual or low vulnerability contexts to investigate such effects and have focused mostly on robot performance. In the present research, we seek to remedy these limitations and compare trust in human-human versus human-robot collaborations in an augmented and adapted version of the Trust Game. We used a mixed factorial design to examine the effects of trust and trust violations on human-human and human-robot interactions over time with an emphasis on anthropomorphic robots in a social context. We found consistent and significant effects of partner behavior. Specifically, partner distrust behaviors led to participants' lower levels of trustworthiness perceptions, trust intentions, and trust behaviors over time compared to partner trust behaviors. We found no significant effect of partnering with a human versus an anthropomorphic robot over time across the three dependent variables, supporting the computers as social actors (CASA; Nass and Moon, 2000) paradigm. This study demonstrated that there may be instances where the effects of trust violations from an anthropomorphized robot partner are not meaningfully different from those of a human partner in a social context. Highlights: Comparison of computers as social agents and unique agent paradigms. Empirically explored the differences in human-human and human-robot interactions across the trust process. No differences found between human-human and human-robot interactions. Furthers the robotics research established in both human-factors psychology and robotics fields.